Cross-neutralization effect of the third dose of inactivated COVID-19 vaccine against the SARS-CoV-2 variants - Yuqing Li; Jiexiao He; Wenqing Liu; Runjie Qi; Jingxin Li; Fengcai Zhu (Expert Review of Vaccines)
Background The ongoing emergence of SARS-CoV-2 variants has raised concerns about the breadth of the immune response provided by existing vaccines.Research design and methods In this study, participants aged 18-75 years with no prior COVID-19 infection or vaccination history were enrolled to receive the CoronaVac vaccine. The interval between the first and second vaccine doses was 28 days, while the third dose was given 6 months after the second.Results Between February 1 to 15 February 2022, we recruited 40 eligible participants who had not received any COVID-19 vaccination and had no prior COVID-19 infection. After the third dose, neutralizing antibody levels significantly increased against the ancestral strain and certain Omicron variants (BA.1, BA.4/5, BF.7). Compared to levels observed 28 days post-second dose, neutralizing antibody levels rose further 28 days after the third dose, with the GMFI against the ancestral strain at 1.69 (95% CI: 1.27, 2.20). Among other variants, the GMFI against Omicron variants (BA.1, BA.4/5, BF.7) exceeded that for Beta and Delta, with the highest GMFI recorded for the BA.4/5 variant at 4.97 (95% CI: 3.08, 8.05).Conclusions The necessity of the third booster dose lies in its ability to enhance the breadth of the immune response.